PERANCANGAN GAME ACTION RPG “NEXT PAGE” DENGAN FITUR AUGMENTED REALITY - Nikolaus Ferdy Tanujaya; Jeanny Pragantha; Rendi Kristyadi (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
“Next Page” is an Augmented Reality game with Action Role Playing Game as its genre. This game created with Unity Game Engine, Vuforia SDK for Augmented Reality feature, and Fungus for storyline. The game is divided into two modes, the story mode and battle mode. In the story mode, player will follow a story line that tell about a boy trapped in a book world. In the battle mode, player will battle enemies in real time action. Player will control the main character to attack the enemies with weapon. This game will be deployed on Android Based Smartphone.